2016
DOI: 10.1016/j.eatbeh.2015.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Food cravings, binge eating, and eating disorder psychopathology: Exploring the moderating roles of gender and race

Abstract: Objective To examine the moderating effects of gender and race on the relationships among food cravings, binge eating, and eating disorder psychopathology in a community sample. Methods Data were collected from a convenience sample of 320 adults (53% male; mean age 28.5±8.2 years; mean BMI 27.1±5.2 kg/m2; mean education 15.1±2.2 years; 64% white, 24% black, and 13% other race) participating in a cross-sectional study examining the interactions between stress, self-control and addiction. Participants complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(46 citation statements)
references
References 63 publications
(76 reference statements)
1
41
0
4
Order By: Relevance
“…Consequently, present results of the effects of online EFT intervention on food cravings cannot be generalized to the adult male population. Although the gender disparity in the current sample aligns with prior research that has found women more likely to experience food cravings than obese males [80,81], and develop mood and anxiety disorders throughout the lifespan [82,83], a more gender-balanced sample should be sought for future research. Finally, in the current study, the age of participants (women) was predominantly between 41 to 60 years.…”
Section: Limitations and Implications For Further Researchmentioning
confidence: 53%
“…Consequently, present results of the effects of online EFT intervention on food cravings cannot be generalized to the adult male population. Although the gender disparity in the current sample aligns with prior research that has found women more likely to experience food cravings than obese males [80,81], and develop mood and anxiety disorders throughout the lifespan [82,83], a more gender-balanced sample should be sought for future research. Finally, in the current study, the age of participants (women) was predominantly between 41 to 60 years.…”
Section: Limitations and Implications For Further Researchmentioning
confidence: 53%
“…Racial and ethnic differences have been found, whereas in Blacks, higher BMI, increased binge‐eating frequency, and faster developmental trajectory of BED has been demonstrated in comparison with White participants . Consumption of a large amount of food is a defining feature of binge eating in examining racial and ethnic differences of the behavior . A recent integrative review evaluating binge eating among racial minority groups reports 83.3% of the studies defined binge eating as the consumption of a large amount of food …”
Section: Resultsmentioning
confidence: 99%
“…For example, in a study by Dye, Warner and Bancroft (1995), there was found the severity of food craving was very strongly related to the reported severity of depression (Dye, Warner and Bancroft,1995). Additionally, gender differences in food cravings and eating behaviours may result from numerous factors including psychological or physiological changes related to menstruation differences in nutrition awareness and knowledge, cultural influences, and differences in dietary and mood-regulating neurotransmitters (Hormes and Timko, 2011;Chao, Grilo, and Sinha, 2016). For example, some researchers have found differences in the prevalence of general food cravings with cravings being more common in females than males (Cepeda-Benito et al, 2003;Lafay et al, 2001), others have found no differences (Burton, Smit, & Lightowler, 2007).…”
Section: Introductionmentioning
confidence: 99%